2017
DOI: 10.1111/febs.14205
|View full text |Cite
|
Sign up to set email alerts
|

RFTS‐dependent negative regulation of Dnmt1 by nucleosome structure and histone tails

Abstract: DNA methylation in promoter regions represses gene expression and is copied over mitotic divisions by Dnmt1. Dnmt1 activity is regulated by its replication foci targeting sequence (RFTS) domain which masks the catalytic pocket. It has been shown that Dnmt1 activity on unmethylated DNA is inhibited in nucleosome cores. In the present study, we aimed to assess the effect of nuclesome formation on maintenance methylation at single CpG resolution. We show that Dnmt1 fully methylates naked linker DNA in dinucleosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(89 reference statements)
0
7
0
1
Order By: Relevance
“…Such heterochromatic and late replicating regions may depend on the dual monoubiquitination of histone H3 via UHRF1 for proper maintenance DNA methylation 16 . It has been shown that hemimethylated DNA wrapped around nucleosomes is not a preferred substrate of DNMT1 17 , and mouse and plant HELLS homologs facilitate methylation of DNA wrapped around nucleosomes in vivo 35 . Therefore, chromatin remodeling by the CDCA7/HELLS complex at heterochromatic and late replicating regions might be required for full methylation by DNMT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such heterochromatic and late replicating regions may depend on the dual monoubiquitination of histone H3 via UHRF1 for proper maintenance DNA methylation 16 . It has been shown that hemimethylated DNA wrapped around nucleosomes is not a preferred substrate of DNMT1 17 , and mouse and plant HELLS homologs facilitate methylation of DNA wrapped around nucleosomes in vivo 35 . Therefore, chromatin remodeling by the CDCA7/HELLS complex at heterochromatic and late replicating regions might be required for full methylation by DNMT1.…”
Section: Discussionmentioning
confidence: 99%
“…and RING finger domains 1 (UHRF1), mediates full methylation at hemimethylated sites in early replicating regions through the dual monoubiquitination of PCNA-associated factor of 15 kDa (PAF15); the same complex targets hemimethylated DNA in late replicating regions through the dual monoubiquitination of the histone H3 tail. Considering that DNMT1 does not prefer hemimethylated DNA wrapped around nucleosomes 17 , we hypothesized that the CDCA7/HELLS complex could facilitate access of the DNMT1/UHRF1 complex to late replicating regions such as pericentromeric repeats to mediate maintenance DNA methylation via chromatin remodeling 12 .…”
mentioning
confidence: 99%
“…Methylation activity measurements using radioisotopes were performed as described . Hemi‐methylated DNA, which is comprised of 42bp and 12 methylated CpG, were used as substrates . In brief, the annealed oligonucleotide (100 nM) was methylated with recombinant Dnmt1 (2 nM), in the presence of 2.2 μM [ 3 H]‐ S ‐adenosyl‐methionine (PerkinElmer Life Sciences) in 25 μL of buffer (5 mM ethylenediaminetetraacetic acid, 20% glycerol, 0.2 mM DTT, 0.2 mM phenylmethylsulfonyl fluoride, and 20 mM Tris•HCl, 7.4) at 37 °C for 1 hour in the presence or absence of the indicated amounts of additives, unless otherwise mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…At these regions, methylation by DNMT1 likely occurs after the wrapping of hemi‐methylated DNA around nucleosomes, because this type of maintenance exhibits much slower kinetics (up to 24 hr) than does replication‐coupled maintenance (Ming et al., 2020 ) and requires multiple mono‐ubiquitylation of histone H3 in nucleosomes by the RING domain of UHRF1 (Nishiyama et al., 2020 ), which stimulates Dnmt1 activity cooperating with the SRA domain of UHRF1 (Mishima et al., 2020 ). As chromatin acts as a barrier to DNA methylation, possibly because hemi‐methylated DNA wrapped around nucleosomes is not a suitable substrate for DNMT1 (Ming et al., 2020 ; Mishima et al., 2017 ), chromatin remodeling was expected to be required for replication‐uncoupled maintenance DNA methylation (Unoki, 2019 ). As expected, it was revealed that HELLS, which forms a chromatin remodeling complex with CDCA7 (Jenness et al., 2018 ), facilitates this type of maintenance by enhancing the chromatin association of UHRF1 (Figure 1b ) (Han et al., 2020 ; Ming et al., 2020 ).…”
Section: Replication‐coupled and Replication‐uncoupled Maintenance Dn...mentioning
confidence: 99%